Ethno-mathematics: Mathematics Embedded in the Traditional Activities of Kumhar Community of the Varanasi District - Pandey, Harish; Bajpai, Anjali (INDIAN EDUCATIONAL REVIEW, 2020)
Various cultural groups have their specific ways of acquiring the useable functional mathematics. They unconsciously apply mathematical skills in their everyday life without realising its significance. Position Paper of National Focus Group on Teaching of Mathematics, NCERT, New Delhi, states that in Indian villages, it is commonly seen that people who are not formally educated use many modes of mental mathematics. These practices of mathematics at local level may be treated as indigenous, oral (vedic), hidden (frozen), and folk mathematics. These different concepts are a part of ethno-mathematics and provide a right of practice to every individual. This paper looks at mathematics used by Kumhar (also known as Prajapati) community, involved in their traditional activities like pot making, carving and selling in different areas of Varanasi district of Uttar Pradesh state. This paper will discuss the steps involved, things used and pattern followed in different types of practices used in pot making and the mathematics embedded in it like the concepts of angle, geometry, mensuration, symmetry, sequencing, Operations Research, reasoning, spiral, conic section, etc. An interview schedule having questions from five areas— biographic information, traditional activities, logic used and Culture, inventory control, and marketing is used and an observation was made for each practices in a naturalistic setting to gather the evidences. Results have implications for teaching of mathematics in a cultural context.